Mediaton Leader Member Exchange, Intrinsic Motivation and Psychological Empowerment the Influence Ethical Leadership on Employee Creativity and Work Innovation - Nurul Ismi; Sumitro Sarkum; Zuriani Ritonga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study examines the effect of ethical leadership style on employee creativity and work innovation by using leader member exchange, intrinsic motivation and psychological empowerment as mediating variables. This type of research is associative research. Data collection in this study was conducted through a survey approach with quantitative descriptive research type by distributing questionnaires to 217 respondents, data collection techniques were carried out by interviews, questionnaires and documentation studies. The data analysis tool used in this study uses SPSS (Statistical Product Software Solution). Instrument Test In this study using Validity Test and Reliability Test. The data analysis technique in this research is descriptive analysis, hypothesis testing. The results showed that the Ethical Leadership variable Affects Intrinsic Motivation, Ethical Leadership Affects Leader Member Exchange, Ethical Leadership Affects Employee Psychological Empowerment, Leader Member Exchange Affects Employee Creativity, Intrinsic Motivation Affects Employee Creativity, Psychological Empowerment Affects Employee Creativity, Employee Creativity Affects Work Innovation.